Isolasi dan Uji Efektivitas Beberapa Isolat Dekomposer Lokal dalam Mendekomposisi Limbah Tanaman Jagung - Nurasiah Djaenuddin; Faesal Faesal; Soenartiningsih Soenartiningsih (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Soil microorganisms are able to digest and degrade organic material present in the environment in to substances that available for plants to absorb. This research aimed to isolate and examine local bacteria that had the ability to decompose corn stover. Soil samples were taken from various natural habitats in which bacteria grow, including remains of corn planting area, pile of waste corncob and corn stalk, pile of rice husk and straw, and pile of used sorghum stalk. Which were collected from several locations across South Sulawesi. Bacteria was isolated by making soil suspension that being inoculated on to NA and CMC medium, and then incubated for 48 hours at room temperature. Bacterial colonies that grow were then incubated 50o C to obtain bacteria resistant to high temperature and able to produce cellulose. Bacterial isolates that produce cellulose was then examined for the effectiveness in decomposing corn stover waste. Isolates result were able to obtain 119 decomposers isolates with 29 isolates resistant to temperature above 50o C and had ability to produce cellulose. From 29 isolates, among 15 isolates collected from rice straw, 5 isolates from remains of corn planting area and 9 isolates collected from several natural habitats. Almost all isolates had good ability to decompose corn stover waste. From isolates tested in corn cob waste and corn leaves waste, only 16 bacterial isolates were proven to be effective as decomposer.